Analisis Penatalaksanaan Interaksi Sosial pada Anak Autis dengan Menggunakan Metode Social Story di Klinik Shally Autis Center Palembang Tahun 2020 - Dewi Puspita Sari; Ayu Novitrie; Latifah Latifah (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Autism is a condition caused by internal disorders. A development characterized by abnormalities in social interactions, communication and very rigid behavior and repetition of behavior, while social interactions are needed in the daily life of children with autism in order to live like everyone else. The purpose of this study was to determine the relationship between eye contact, understanding, emotions, and speech on the social interactions of children with autism. This research is an analytic survey with a Cross sectional design. The population in this study were all 60 patients diagnosed with autism at the Shally Autis Center palembang. the sample in this study was the total of population, namely 60 children. The results of the study found that there was a relationship between eye contact, understanding, emotions, and speech with the social interaction of children with autism at the Shally Autis Center Palembang clinic in 2020. At the end of the study it is suggested that therapists in increasing social interaction of children with autism should pay attention to aye contact, understanding, emotion, and speech to be promoted for better development.